Circulating Type I Interferon Levels in the Early Phase of COVID-19 Are Associated With the Development of Respiratory Failure - Nagaoka, Kentaro; Kawasuji, Hitoshi; Murai, Yushi; Kaneda, Makito; Ueno, Akitoshi; Miyajima, Yuki; Fukui, Yasutaka; Morinaga, Yoshitomo; Yamamoto, Yoshihiro (Frontiers in Immunology, 2022)
Background: The role of type I interferons (IFNs) in the early phase of COVID-19 remains unclear. Objectives: To evaluate the relationship of IFN-I levels in patients with COVID-19 to the clinical presentation, SARS-CoV-2 viral load, and other major pro-inflammatory cytokines. Methods: This prospective observational study recruited consecutive patients hospitalized with COVID-19. The blood levels of IFN-α and IFN-β within 5 days after symptom onset were validated using ELISA, as were those of other cytokines, including IL-6 and CXCL10. The SARS-CoV-2 viral load was determined via qPCR using nasal-swab specimens and blood serum. Results: The study enrolled 50 patients with COVID-19. IFN-α levels were significantly higher in patients who presented with pneumonia or developed hypoxemic respiratory failure (p < 0.001). Furthermore, IFN-α levels correlated with the viral load in nasal-swab specimens and the presence of RNAemia (p < 0.05). In contrast, IFN-β levels did not correlate with the presence of pneumonia or RNAemia, despite showing a stronger correlation with the nasal-swab viral load (p < 0.001). Correlation analysis showed that the serum levels of IFN-α significantly correlated with those of IFN-β, IL-6, and CXCL10, while the levels of IFN-β did not correlate with those of IL-6 or CXCL10. Conclusions: Serum IFN-I levels in the early phase of SARS-CoV-2 infection were higher in patients who developed hypoxemic respiratory failure. The strong association among IFN-α, IL-6, and CXCL10 possibly reflects the systemic immune response against SARS-CoV-2 invasion into the pulmonary circulation, which might be an early predictor of respiratory failure due to COVID-19.